Supercritical water gasification of lignin solution produced by steam explosion process on Arundo Donax after alkaline extraction. (1st June 2018) - Molino, A.; Larocca, V.; Valerio, V.; Rimauro, J.; Marino, T.; Casella, P.; Cerbone, A.; Arcieri, G.; Viola, E.
Abstract: In this paper the lignin gasification by using water in supercritical was studied. The employed lignin was produced via steam explosion of Arundo Donax after alkaline extraction and filtration. The lignin, with a total solid content of about 4 wt% in a solution of sodium hydroxide which confers to the solution a pH of about 11, was fed in a continuous PFR bench scale reactor able to operate at supercritical water conditions. The experiments were carried out at 550 °C and 250 bar by varying the feed flow rate from 10 mL/min to 60 mL/min in order to understand the effect of the residence time on the liquid and solid phases in terms of volume composition, liquid phase composition, carbon and global gasification efficiency. The main results showed that by using lignin after alkaline extraction, syngas with a higher heating value (HHV) greater than 40 MJ/kg without CO2, mainly composed by hydrogen and methane, was obtained. At the same time, in the liquid phase the presence of some compounds, such as glucose, syringaldehyde, formic acid, acetic acid and xylose, was revealed, and all these species are included in the main building block group for the green chemistry or for the development of bioprocess for high added value intermedia production.